Does Financial Literacy and Attitudes Influence Financial Management Behavior in The MSME'S Sector? - Fauzan; Fadya Almira; Erma Setiawati; Agus Endro Suwarno (Riset Akuntansi dan Keuangan Indonesia, 2023)
Financial management behavior is considered to be one of the essential concepts in economics, such US allocation of financial resources and utilization This study aims to analyze the effects of financial literacy, financial attitudes, and the use of finance resources. and income on financial management behavior (case studies on MSMEs in the trade sector in Surakarta). This study used a quantitative approach method. The sampling technique used in this study was purposive sampling with 90 MSMEs business owners who are engaged in trade with food & beverage, fashion, and grocery businesses. The source used was primary data by deploying questionnaires that were then analyzed using multiple linear regression analysis with IBM SPSS Statistics 26 software. Based on the results of the data processing conducted, the result that financial literacy variables have a significant effect on financial management behavior, financial attitudes have no effect on financial management behavior, and income has a significant effect on financial management behavior. With good financial management behavior will help MSMEs actors in preparing short-term and long-term financial planning and can be responsible for financial management of money and assets that are considered productive.